Old Code Subject Files V
The series includes daily press releases, newspaper clippings from Czechoslovak, German, and British periodicals, transcripts of the monitoring of the Czechoslovak Radio and Television broadcasts, Background Reports Situation Reports and RFE Research Reports. Includes extensive information related to agriculture, armed forces, political parties (large section on the Communist Party - the files on the Central Committee are from1946), opposition, economy, culture, industry and state apparatus.. The files regarding the criticism of and reaction to the regime, dissent and persecution as well as the files relating to 1968 events are useful cross-references to Collection of documents on 1968 and Collection of records relating to the Czechoslovak Opposition and Protest Movement.